Criminal Liability Mechanism for Corporations That Do Not Register Their Workers' Health Insurance After the Birth of The Job Creation Law - Chandra Syahputra; Muhammad Arifin; Onny Medaline (Lembaga Riset Mutiara Akbar, 2025)
Protection of workers’ rights is a vital aspect of implementing social security in Indonesia. The enactment of Law Number 11 of 2020 concerning Job Creation brought significant changes to labor law, including adjustments to the mechanism of social security implementation previously governed by Law Number 24 of 2011 concerning the Social Security Administration Agency (BPJS). Using a normative juridical method with legislative, conceptual, and case approaches, this study analyzes secondary data from laws, doctrines, and court decisions. The findings show that despite the Job Creation Law reaffirming corporate obligations to register workers in social security programs, many corporations still neglect this duty due to weak supervision and limited enforcement. Administrative sanctions are strengthened, but criminal sanctions remain subsidiary and rarely applied. Obstacles to corporate criminal liability include difficulties in proving corporate intent, limited technical procedures for investigation, and weak coordination among authorities. The study recommends clearer implementing regulations to define corporate fault, representative liability, and proportional sanctions.